Low-heat-production high-specific-energy lithium ion capacitor
By using materials such as lithium iron phosphate, lithium manganese iron phosphate and activated carbon as positive and negative electrode materials, combined with high ionic conductivity electrolyte, the problems of heat accumulation and low energy density of existing lithium-ion batteries and supercapacitors under high power are solved, and lithium-ion capacitors with high energy density, low heat generation and long cycle life are achieved.
Patent Information
- Application Number
- CN202511003396.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-09-12
AI Technical Summary
Existing lithium-ion batteries can easily pose a safety risk due to heat accumulation under high power, and supercapacitors have low energy density and cannot meet the data center's requirements for high energy density, low heat generation and long cycle life.
Lithium iron phosphate, lithium manganese iron phosphate and activated carbon are used as positive electrode materials, hard carbon, activated carbon and mesophase carbon microspheres are used as negative electrode materials, combined with a carbonate electrolyte with high ionic conductivity to form a low heat generation and high specific energy lithium ion capacitor.
The energy density of lithium-ion capacitors has been significantly improved from 6.4Wh/kg to 70Wh/kg, the temperature rise during the cycle has been reduced, and the safety and stability have been greatly improved.
Smart Images

Figure BDA0005509593300000051 
Figure HDA0005509593310000011 
Figure HDA0005509593310000012
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a lithium-ion capacitor with low heat generation and high specific energy. Background Art
[0002] With the increasingly prominent characteristics of ultra-high proportion of new energy power access and weak grid strength, the daily power fluctuation range is large, and the energy storage system has put forward higher requirements for short-term and rapid power regulation. Since 2025, the development and application of AI technology has been in full swing, and artificial intelligence data centers have flourished. The development of AI technology is inseparable from high-performance GPU adaptation. It is urgently needed to configure a power supply that can instantly (millisecond level) absorb / release high power and has backup power capability. Otherwise, it is very easy to cause power spikes or grid failures in the data center, causing huge economic losses.
[0003] The current power output characteristics and cycle life of lithium-ion batteries are no longer able to meet the requirements, and heat accumulation under high power can easily create a high safety risk, which is contrary to the power supply safety principles of data centers; the energy density of double-layer supercapacitors is relatively low, about 10Wh / kg, less than 20% of that of lithium-ion capacitors. As a result, double-layer supercapacitors of the same power are too large compared to lithium-ion capacitors and cannot be integrated into cabinets.
[0004] Patent CN 119724944A discloses a hybrid energy storage device with high energy density and long cycle life. The positive electrode material used is a powder formed by layered lithium-containing metal oxide and activated carbon in parallel. The lithium nickel cobalt manganese oxide NCM system compound is added with lithium cobalt oxide LCO or lithium-rich manganese-based oxide. Compared with polyanion positive electrode materials (LiFePO4, LiFe x Mn 1-y PO4), layered lithium-containing oxides have poor thermal stability and are prone to oxygen evolution reaction under high voltage, posing a great safety risk.
[0005] Patent CN 107248451 B discloses a high-energy-density lithium-ion capacitor. Its positive electrode utilizes a high-surface-area carbon material, and its negative electrode utilizes a silicon-carbon composite material (one of the raw materials is 10-micron silicon powder). The silicon-carbon composite material, produced by ball milling and sand milling, has a maximum silicon particle size of 100 to 150 nanometers, but still exhibits significant volume expansion. Consequently, the silicon-carbon composite electrode is prone to material pulverization and shedding during long-term cycling, making it difficult to maintain high energy density.
[0006] Lithium-ion capacitors (LICs) combine the advantages of both LIBs and supercapacitors, offering high power density and cycle life while maintaining high energy density. They are a prominent alternative to supercapacitors and possess a broad range of applications and market prospects. Therefore, to meet the demands of AI data centers for advanced computing power, which requires high energy consumption, instantaneous power, and energy stability, there is an urgent need to develop LICs with high energy density, high power density, and low heat generation for long cycles. Summary of the Invention
[0007] In order to overcome the shortcomings of the prior art in which heat accumulation of lithium-ion batteries at high power easily creates a high safety risk and supercapacitors have a relatively low energy density, the present invention provides a low-heat-generating, high-specific-energy lithium-ion capacitor that combines the advantages of lithium-ion batteries and supercapacitors, providing higher power density and cycle life while maintaining high energy density, solving the problems of low power density and short cycle life of lithium-ion batteries and low energy density of supercapacitors, while improving low-temperature performance.
[0008] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:
[0009] A low-heat-generation, high-energy-density lithium-ion capacitor, characterized in that it consists of a shell, a positive electrode sheet, a negative electrode sheet, a separator between the positive and negative electrode sheets, and an electrolyte. The positive electrode sheet is manufactured by coating a slurry containing a positive electrode active material, a conductive agent, and a binder onto an aluminum foil; the negative electrode sheet is manufactured by coating a slurry containing a negative electrode active material, a conductive agent, and a binder onto a copper foil; the positive electrode active material consists of lithium iron phosphate, lithium manganese iron phosphate, and a first activated carbon, with a mass proportion of 50% to 90%, 0% to 30%, and 0% to 20%, respectively; the negative electrode active material consists of hard carbon, a second activated carbon, and mesophase carbon microbeads, with a mass proportion of 70% to 95%, 5% to 30%, and 0% to 20%, respectively.
[0010] The lithium iron phosphate is a small-particle, high-density, high-capacity material with a median particle size of 0.7 μm to 1.5 μm and a compaction density of 2.60 g / cm 3 ~2.85g / cm 3 The median operating voltage of lithium manganese iron phosphate is 3.4V~3.9V.
[0011] The specific surface area of the first activated carbon and the second activated carbon is 1400m 2 / g~3100m 2 / g, the micropore volume proportion of the first activated carbon is 55% to 75%, and the micropore volume proportion of the second activated carbon is 75% to 90%.
[0012] The porosity of the diaphragm is 40-70%, the electrolyte is a carbonate lithium salt electrolyte, and the ion conductivity is greater than 10S / cm.
[0013] The conductive agent is selected from at least one of conductive carbon black and carbon nanotubes. The binder used in the positive electrode sheet is polyvinylidene fluoride; the binder used in the negative electrode sheet is sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0014] The positive electrode sheet, separator and negative electrode sheet are sequentially stacked or wound and assembled.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The lithium-ion capacitor of the present invention uses polyanionic lithium iron phosphate and lithium iron manganese phosphate as positive electrode materials, which have the advantages of small volume expansion, good thermal stability and safety, and high specific capacity. The energy density of the device is increased from 6.4Wh / kg to 70Wh / kg, an increase of one order of magnitude.
[0017] 2. The lithium-ion capacitor of this invention incorporates activated carbon on either the positive or negative electrode side, achieving high energy density, capacity stability, and safety at high power. The temperature rise during cycling is significantly reduced from 17.8°C to 2.2°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the cycle performance diagram of Example 1;
[0019] Figure 2 The figure shows the change of battery surface temperature during the cycle process. DETAILED DESCRIPTION
[0020] The following examples are illustrative descriptions of the primary experimental evidence, and are not intended to limit the core content and scope of application of the present invention to the amount of evidence. It should be noted that all of the accompanying drawings and corresponding descriptions only illustrate the concepts, principles, and representative experimental evidence of the embodiments disclosed in the present invention. If the chain of evidence is complete, it is not necessary to present all the specific details and extended details of each embodiment listed in the present invention.
[0021] Unless otherwise defined, the technical terms used in the following examples have the same meanings as commonly understood by those skilled in the art. The experimental reagents used in the following examples, unless otherwise specified, are conventional biochemical reagents; and the experimental methods described, unless otherwise specified, are conventional methods.
[0022] A low-heat-generating, high-energy-density lithium-ion capacitor consists of a housing, a positive electrode sheet, a negative electrode sheet, a separator between the two sheets, and an electrolyte. The negative electrode sheet, the positive electrode sheet, and the separator between the two sheets are stacked or wound to form a battery cell. The positive electrode sheet is manufactured by applying a slurry containing the positive electrode active material, a conductive agent, and a binder onto aluminum foil. The negative electrode sheet is manufactured by applying a slurry containing the negative electrode active material, a conductive agent, and a binder onto copper foil. The positive electrode material consists of lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), and a first activated carbon (AC1), with the mass proportions of LFP, LMFP, and AC1 being 50%-90%, 0%-30%, and 0%-20%, respectively. The negative electrode active material consists of hard carbon (HC), a second activated carbon (AC2), and mesocarbon microbeads (MCMB), with the mass proportions of HC2, AC2, and MCMB being 70%-95%, 5%-30%, and 0%-20%, respectively. The binder used for the positive electrode sheet is polyvinylidene fluoride (PVDF), while the binder used for the negative electrode sheet is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The conductive agent is selected from conductive carbon black (SP) and carbon nanotubes (CNTs). The separator has a porosity of 40%-70%, and the electrolyte is a carbonate-based lithium salt electrolyte with an ionic conductivity >10 S / cm.
[0023] Example 1:
[0024] The active materials of the positive electrode are LFP, LMFP, and AC1, with the mass proportions of the three being 50%, 30%, and 20% respectively. The mass ratios of LFP:LMFP:AC1:SP:CNT:PVDF are 46.5:27.9:18.6:3:1.5:2.5. The active materials in the negative electrode sheet are HC and AC2, with the mass proportions of the two being 90% and 10% respectively. The mass ratios of HC:AC2:SP:CNT:CMC:SBR are 79.2:8.8:3.0:3.0:2.4:3.6. The median particle size of LFP is 0.7μm and the compacted density is 2.65g / cm 3 The median operating voltage of LMFP is 3.4V; the specific surface areas of AC1 and AC2 are 1876m 2 / g、2500m 2 / g, the volume proportion of micropores in AC1 is 55%, and the volume proportion of micropores in AC2 is 90%. The prepared positive electrode sheet, negative electrode sheet and separator are wound to make a lithium ion capacitor. The mass ratio of positive electrode active material to negative electrode active material is 1.00:1.20, the porosity of the separator is 40%, and the electrolyte is composed of ethyl carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The ion conductivity is 11.5S / cm. The test shows that within the voltage range of 2.2V to 3.65V, the energy density of the battery cell can reach 70Wh / kg; if Figure 1As shown in Figure 1, the capacity can still be maintained at 84.6% after 1000 cycles of constant power charge and discharge at 7kW / L. Figure 2 As shown in the figure, the temperature of the battery cell increased from 25°C to 27.2°C before and after the cycle, with a temperature increase of 2.2°C.
[0025] Example 2:
[0026] The positive electrode active materials are LFP and LMFP, with a mass ratio of 70% and 30% respectively, and a mass ratio of LFP:LMFP:SP:PVDF of 66.15:28.35:3.0:2.5. The negative electrode active materials are HC and AC2, with a mass ratio of 95% and 5% respectively, and a mass ratio of HC:AC2:SP:CNT:CMC:SBR of 83.6:4.4:3.0:3.0:2.4:3.6. The median particle size of LFP is 1.5μm and the compacted density is 2.60g / cm 3 The median operating voltage of LMFP is 3.9V; the specific surface area of AC2 is 1400m 2 / g, the volume of micropores in AC2 accounts for 75%. The prepared positive electrode sheet, negative electrode sheet and diaphragm laminate are made into lithium ion capacitors. The mass ratio of positive electrode active material to negative electrode active material is 1.00:1.25, the porosity of the diaphragm is 70%, and the electrolyte is composed of ethyl carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The ion conductivity is 10.4S / cm. The test results show that within the voltage range of 2.2V to 3.8V, the energy density of the battery cell can reach 85Wh / kg; at 25℃, 7kW / L constant power charge and discharge, the capacity can still maintain 60.7% after 1000 cycles; such as Figure 2 As shown in the figure, the surface temperature of the lithium-ion battery increased from 25°C to 42.8°C, with a temperature rise of 17.8°C.
[0027] Example 3:
[0028] The active materials of the positive electrode are LFP and AC1, with the mass proportions of the two being 90% and 10% respectively. The mass ratio of LFP:SP:CNT:PVDF is 85.05:9.45:1.5:1.5:2.5. The active materials in the negative electrode sheet are HC, AC2, and MCMB, with the mass proportions of the three being 70%, 10%, and 20% respectively. The mass ratios of HC:AC2:MCMB:SP:CNT:CMC:SBR are 62.3:8.9:17.8:2.0:3.0:2.4:3.6. The median particle size of LFP is 0.7μm; the compacted density is 2.65g / cm 3 ; The specific surface area of AC2 is 23500m 2 / g、3100m 2 / g, with the volume proportion of micropores in AC1 and AC2 being 60% and 82%, respectively. The diaphragm porosity is 55%, and the electrolyte consists of ethyl carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, with an ionic conductivity of 10.4S / cm. The prepared positive and negative electrode sheets were stacked to form a lithium-ion capacitor, with a mass ratio of positive to negative active materials of 1.00:1.20. Tests showed that within the voltage range of 2.2V to 3.65V, the cell energy density can reach 73Wh / kg. As shown in Table 1, at a constant power of 7kW / L, the capacity can still be maintained at 72.3% after 1000 cycles. Comparing the temperature changes during the cycling process, the cell temperature increased by 9.6°C.
[0029] Example 4:
[0030] The positive electrode active materials are LFP and AC1, with the mass proportions of the two being 80% and 20% respectively. The mass ratio of LFP, AC1:SP:CNT:PVDF is 75.2:18.8:2:1.5:2.5. The median particle size of LFP is 1.2μm; the compaction density is 2.85g / cm 3 The active materials in the negative electrode sheet are HC and AC2, with a mass ratio of 70%:30%. The mass ratio of HC:AC2:MCMB:SP:CNT:CMC:SBR is 61.6:26.4:1.0:2.0:3.0:2.4:3.6. The specific surface areas of AC1 and AC2 are 1400m 2 / g、3100m 2 / g, the micropore volume proportions in AC1 and AC2 were 75% and 75%, respectively, the separator porosity was 60%, and the electrolyte consisted of ethyl carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, with an ionic conductivity of 11.2 S / cm. The prepared positive and negative electrode sheets were wound to form a lithium-ion capacitor, with a mass ratio of positive to negative active material of 1.00:1.20. Testing showed that the cell energy density reached 55 Wh / kg within the voltage range of 2.2V to 3.65V. As shown in Table 1, after 1000 cycles of charge and discharge at a constant power of 7kW / L, the capacity still maintained 67.2%. Comparing the temperature changes during the cycling process, the cell temperature increased by 5.8°C.
[0031] Example 5: Comparative Example 1
[0032] The active material in the positive electrode sheet is LFP, accounting for 100% by mass. The mass ratio of LFP:SP:CNT:PVDF is 90:4.5:1.5:1.5:2.5, and the median LFP particle size is 0.7μm. The active material in the negative electrode sheet is graphite (Gr), and the mass ratio of Gr:SP:CMC:SBR is 94.5:2.0:1.5:2.0. The prepared positive and negative electrode sheets are stacked to form a lithium-ion battery. The battery cell energy density can reach 88Wh / kg, and the constant power charge and discharge cycle life at 7kW / L is only 187 times. During constant power discharge at 7kW / L, the surface temperature of the lithium-ion battery rises from 25°C to 45.9°C, a temperature rise of 20.9°C.
[0033] Example 6: Comparative Example 2
[0034] The active material in the positive electrode sheet is AC1, accounting for 100% by mass, with a mass ratio of AC1:SP:CNT:PVDF of 94.5:1.5:1.5:2.5. The active materials in the negative electrode sheet are HC and AC2, with a mass ratio of 90%:10%, and a mass ratio of HC:AC2:SP:CNT:CMC:SBR of 79.2:8.8:3.0:3.0:2.4:3.6. The prepared positive and negative electrode sheets are stacked to form a lithium-ion capacitor, with a cell energy density of only 6.4Wh / kg.
[0035] Table 1 Comparison table of various embodiments and comparative examples
[0036]
[0037] As shown in Table 1, by comparing Comparative Example 1 with Example 2, it can be seen that after using hard carbon and activated carbon at the negative electrode, the capacitive adsorption and desorption mechanism effectively improves the power characteristics of the device, and the cycle stability and heat generation characteristics under high power are significantly improved; by comparing Example 2 with Examples 1, 3-4, after adding activated carbon to the positive electrode, the temperature rise during the cycle is significantly reduced, which can be reduced from 17.8°C to 2.2°C; by comparing Examples 3 and 4, it can be seen that as the amount of activated carbon on the positive and negative electrode sides increases, the cycle temperature rise also shows a downward trend (from 9.6°C to 5.8°C); the above comparison fully demonstrates the performance advantages of the present invention in terms of low heat generation, which can improve safety characteristics.
[0038] Comparing Comparative Example 2 with Example 1, we can see that adding LFP to the positive electrode increases the device's energy density from 6.4 Wh / kg to 70 Wh / kg, an order of magnitude improvement. These results demonstrate that the present invention provides an effective technical solution for low-heat-generating, high-energy-density lithium-ion capacitors.
[0039] The above embodiments describe only a portion of the specific implementation methods of the present invention in detail and are not limited to the embodiments disclosed herein. Furthermore, the substantive content protected by the present invention is not limited thereto. Any other modifications, equivalent replacements, and improvements based on the concepts, principles, and technical approaches of the present invention, without departing from the scope of the present invention, fall within the scope of protection of the present invention.
Claims
1. A low heat generation and high specific energy lithium ion capacitor, characterized in that: It consists of a shell, a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte between the positive and negative electrode sheets. The positive electrode sheet is manufactured by applying a slurry containing a positive electrode active material, a conductive agent and a binder onto an aluminum foil; the negative electrode sheet is manufactured by applying a slurry containing a negative electrode active material, a conductive agent and a binder onto a copper foil; the positive electrode active material is composed of lithium iron phosphate, lithium manganese iron phosphate and a first activated carbon, with a mass proportion of 50% to 90%, 0% to 30% and 0% to 20% respectively; the negative electrode active material is composed of hard carbon, a second activated carbon and mesophase carbon microbeads, with a mass proportion of 70% to 95%, 5% to 30% and 0% to 20% respectively.
2. The low heat generation and high specific energy lithium ion capacitor according to claim 1, characterized in that: The lithium iron phosphate is a small-particle, high-density, high-capacity material with a median particle size of 0.7 μm to 1.5 μm and a compaction density of 2.60 g / cm 3 ~2.85g / cm 3 The median operating voltage of lithium manganese iron phosphate is 3.4V~3.9V.
3. The low heat generation and high specific energy lithium ion capacitor according to claim 1, characterized in that: The specific surface area of the first activated carbon and the second activated carbon is 1400m 2 / g~3100m 2 / g, the micropore volume proportion of the first activated carbon is 55% to 75%, and the micropore volume proportion of the second activated carbon is 75% to 90%.
4. The low heat generation and high specific energy lithium ion capacitor according to claim 1, characterized in that: The porosity of the diaphragm is 40-70%, the electrolyte is a carbonate lithium salt electrolyte, and the ion conductivity is greater than 10S / cm.
5. The low heat generation and high specific energy lithium ion capacitor according to claim 1, characterized in that: The conductive agent is selected from at least one of conductive carbon black and carbon nanotubes. The binder used in the positive electrode sheet is polyvinylidene fluoride; the binder used in the negative electrode sheet is sodium carboxymethyl cellulose and styrene-butadiene rubber.
6. The low heat generation and high specific energy lithium ion capacitor according to any one of claims 1 to 5, characterized in that: The positive electrode sheet, separator and negative electrode sheet are sequentially stacked or wound and assembled.
Citation Information
Patent Citations
A high energy density lithium-ion capacitor
CN107248451B
Hybrid energy storage device with high energy density and long cycle life
CN119724944A